Effectiveness of Scoring Systems in Preventing Abdominal Trauma Emergencies - Dance Nong Daniel nong dance; Sriyono Sriyono; Erna Dwi Wahyuni; Siska Ayu (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Abdominal trauma is one of the leading causes of morbidity and mortality in emergency cases, with an incidence rate of 7-10% of all trauma cases. Accurate and timely assessment is crucial to determine the need for surgical intervention and prevent fatal complications. Evaluating the effect of scoring system-based abdominal assessment instruments on the prevention of emergencies and patient clinical outcomes. A systematic review of quantitative studies was conducted. Full-text articles were retrieved from four databases: Web of Science, ScienceDirect, ProQuest, and PubMed for the period 2020-2025. The keywords used were: Abdominal Trauma OR Abdominal Injury AND Assessment OR Scoring OR Initial Assessment OR Preliminary OR Evaluation AND Emergency. The quality of the studies was assessed using the Joanna Briggs Institute (JBI) criteria. A narrative analysis was conducted to present the effectiveness of scoring-based abdominal assessment in preventing emergencies. A comprehensive analysis of 15 studies evaluated five major scoring systems: CASS, BATSS, ISS, RTS, and TRISS. BATSS showed the best diagnostic performance with excellent surgical intervention prediction capabilities, achieving sensitivity of up to 100% and specificity of nearly 97%. CASS showed wider performance variability but still provided satisfactory prediction accuracy. ISS proved effective in predicting morbidity and mortality, with critical values indicating very high-risk patients. TRISS demonstrated superior performance as a predictor of mortality with near-perfect prediction accuracy, making it a highly reliable instrument for mortality risk stratification. Abdominal assessment instruments based on scoring systems significantly influence the prevention of emergencies through early identification of high-risk patients, optimization of the use of diagnostic modalities such as CT scans, and facilitation of timely clinical decision-making. BATSS shows superiority in predicting the need for surgical intervention, while TRISS excels in predicting mortality. Implementation of this scoring system can improve the quality of triage and initial management of abdominal trauma in the emergency room. Keywords: Abdominal Trauma , Assestment,  Emergency.